Can Calvary Survive? - T., Mahendran (1997)
Since the beginning of March 1997, the production situation at Calvary had become critical. Suddenly, they were faced with an apparently insurmountable task of meeting the increased requirements for the domestic market, over the already increased demand for production time placed on them by the export orders and the critical shortage of stocks in government hospitals. The increased demand for the domestic sector was attributed to the fact that plans implemented by the management of Danco Pharmaceutical, were just coming on-stream. Since the acquisition of Calvary Industries towards the end of 1996, the business plan for the coming years had spelt for the up-scaling of domestic sales from RM29 million in 1996 to about RM13.75 million by the year 2000. The immediate requirements of Danco Pharmaceutical called for production to meet a sales budget of RM5.5 million in 1997, if the plan of RM13.75 million was to be achieved. The inventory level as at January 15 1997 was valued at RM 285,000 and the situation was so bad that up to RM75,000 worth of sales were in back-order. It was evident that something had to be done fast enough to achieve desirable inventory levels. Furthermore, Danco Pharmaceutical had embarked on an image building course and quality was being emphasised, from both the perspective of the products it marketed and the services it provided.